THE EFFECTIVENES OF APPLYING MINI CLUSTER FORUM TOWARD STUDENT’S READING COMPREHENSION - moh izzatul ulum (Graduate Program, University of Islam Malang, 2020)
This investigation goal is to investigate and to answer of applying mini cluster forum in the classroom against student’s reading understanding. This enquiry was administered at Eleventh grade of SMK Darussalam Blokagung Banyuwangi. In this case, the researcher used quantitative research namely Quasi-Experiment so that it’s needed a sample of population at this school namely XI AK 1 as control class and XI AK 2 as treatment class. In treatment class, the researcher utilized mini cluster forum strategy to understand a literature or written text and used big cluster forum in control class. Besides that, there were two steps in this study to obtain data namely by holding pretest and posttest. The yield showed that the students instructed by exercising mini cluster forum got enhancement in comprehending of a written text. It meant that mini cluster forum was significant.Keywords: mini cluster forum, reading comprehension